USING SCANNING TECHNIQUE IN READING AT THE ELEVENTH GRADE OF SMK TIWIKRAMA MAMUJU - Enni Enni (Universitas Muhammadiyah Enrekang, 2020)
The objective of the research is to find out the use scanning technique effective in improving the Students’ Reading Ability at the eleventh grade students’ of SMK Tiwikrama Mamuju. This research took place at SMK Tiwikrama Mamuju which the researcher used pre-experimental. Population of research was the eleventh grade students of SMKTiwikrama in academic year 2019/2020. Sample of the research was 30 students that take by purposive sampling technique. The researcher used reading test as instrument of the research. Result of data analysis showed that t-table value at n-1 = 30-1=29 (at significant level α = 0,05) was 2,045 and t-test value was 25,57. It showed t-test was higher than t-table, it meant that null hypothesis was rejected and alternative hypothesis was accepted. Therefore, the researcher concluded that the use of Scanning technique could improve the students’ reading ability at the eleventh gradeof SMK Tiwikrama. It was supported result of students’ mean score at pre-test and post-test. Which mean score of pre-test was 49,17(very poor score) improved to 75 (good score) at the post-test.